Parenting young athletes the Ripken way : ensuring the best experience for your kids in any sport - Ripken, Cal, Jr., 1960- (Gotham Books, 2006)
Few athletes embody sportsmanship and class as perfectly as Cal Ripken, Jr. Since he retired from baseball in 2001, Ripken has devoted his time to coaching kids, including his own two children. But Ripken is troubled by what he sees in youth sports: a competitive intensity that removes the element of fun from playing. Drawing from his experiences as a father, a player, and a coach, the legend offers his insights and advice here, including: how an overemphasis on winning can harm your child's game; why it's counterproductive to correct your child's technique during a game; how Ripken's techniques can be applied to other sports; and much more. Showcasing his proven philosophy (keep it simple, explain the "why," celebrate the individual, and make it fun!), Ripken has created a plan that will delight baseball lovers for generations to come.--From publisher description.